2017
DOI: 10.3171/2016.6.spine151477
|View full text |Cite
|
Sign up to set email alerts
|

The effect of posterior polyester tethers on the biomechanics of proximal junctional kyphosis: a finite element analysis

Abstract: OBJECTIVE Proximal junctional kyphosis (PJK) remains problematic following multilevel instrumented spine surgery. Previous biomechanical studies indicate that providing less rigid fixation at the cranial aspect of a long posterior instrumented construct, via transition rods or hooks at the upper instrumented vertebra (UIV), may provide a gradual transition to normal motion and prevent PJK. The purpose of this study was to evaluate the ability of posterior anchored po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 28 publications
4
93
2
Order By: Relevance
“…Such biomechanical alterations have been shown to be further aggravated by the removal of supraspinous and interspinous ligaments. 2,3 MT restricted motion only under extension loads and reduced DIDP only under flexion and torsion moments at the UIV+1 level. As shown in Fig.…”
Section: Current Study-biomechanical Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…Such biomechanical alterations have been shown to be further aggravated by the removal of supraspinous and interspinous ligaments. 2,3 MT restricted motion only under extension loads and reduced DIDP only under flexion and torsion moments at the UIV+1 level. As shown in Fig.…”
Section: Current Study-biomechanical Analysismentioning
confidence: 92%
“…These pathologic forces result in increases in angular displace- ment and intradiscal pressure that lead to PJK. [2][3][4] Based on these studies, local biomechanical factors have been identified that can favorably influence these parameters. These factors include preservation of soft tissue elements, the presence of an anchor at the UIV, and the use of a transitional rod, as well as rod curvature and diameter.…”
Section: Preclinical Pjk Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent finite element analysis found that polyester tether reinforcement of the posterior elements was able to successfully reduce adjacent segment stress at levels above the upper instrumented vertebrae (UIV). 20 Other authors have described a semitendinosus graft to augment the posterior spinous ligament at the UIV. 21 In our practice, we utilize a surgical nylon tape (SNT) to reinforce the PLS at the UIV in select cases.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic positioning of X‐ray imaging of cervical spine flexion and extension can provide a good reference for the upper cervical spine, and it can also indicate that upper cervical spine instability occurs in the movement process of the cervical spine. However, the currently popular medical‐imaging methods cannot accurately capture and describe the overall process and dynamic characteristics of upper cervical spine instability.…”
Section: Introductionmentioning
confidence: 99%